Sequence Impedance Modeling and Optimization of MMC-HVDC Considering DC Voltage Control and Voltage Feedforward Control - Tong Huang; Xin Chen (Energies, 2022)
The dynamic performance of the DC bus significantly influences the impedance characteristics of MMC and the system stability in a high-voltage direct current system. However, most of the existing MMC-HVDC system stability research simplifies the DC side as an ideal voltage source and ignores the impacts of voltage feedforward control, which affects the accuracy and practicability of stability analysis. In this paper, a sequence impedance model considering both DC voltage control and voltage feedforward control is developed, and the necessity of considering DC control and voltage feedforward control for MMC-HVDC stability analysis is illustrated. Then, the impact of control parameters on MMC-HVDC impedance is discussed, and the boundary conditions of control parameters are also derived. Finally, a method of control parameters design and impedance optimization for MMC-HVDC based on the stability boundary is proposed. Compared to the traditional optimization method, the system stability is further improved by the impedance optimization method proposed this paper.